The Probiotics in Pediatric Asthma Management (PROPAM) Study in the Primary Care Setting: A Randomized, Controlled, Double-Blind Trial with Ligilactobacillus salivarius LS01 (DSM 22775) and Bifidobacterium breve B632 (DSM 24706) - Lorenzo Drago; Luigi Cioffi; Maria Giuliano; Marco Pane; Angela Amoruso; Irene Schiavetti; Gregor Reid; Giorgio Ciprandi; null PROPAM Study Group (Journal of Immunology Research)
Background. Type-2 inflammation commonly marks asthma in childhood. Also, gut and lung dysbiosis is detectable in patients with asthma. Strain-related probiotic supplementation may restore a physiological immune response, dampen airway inflammation, and repair dysbiosis. Therefore, the probiotics in pediatric asthma management (PROPAM) study is aimed at demonstrating that Ligilactobacillus salivarius LS01 (DSM 22775) and Bifidobacterium breve B632 (DSM 24706) mixture could reduce asthma exacerbations in children, followed in a primary care setting. Methods. The study was randomized, placebo-controlled, and double-blind. It involved 11 Italian primary care pediatricians. The probiotic mixture (containing Ligilactobacillus salivarius LS01 1×109 live cells and Bifidobacterium breve B632 1×109 live cells) or placebo was taken twice daily (1 sachet in the morning and 1 in the evening) for eight weeks and subsequently once daily for a further eight weeks. Outcomes included number, severity, and duration of asthma exacerbations, intensity of maintenance and as need treatments, and safety. Results. The per-protocol population included 422 children (mean age seven years, 240 males and 182 females). The probiotic mixture significantly reduced the number of asthmatic exacerbations (OR=3.17). In addition, the number of children with two exacerbations was less than a third in the active group (OR=3.65). Conclusions. This PROPAM study demonstrated that probiotic strains Ligilactobacillus salivarius LS01 (DSM 22775) and Bifidobacterium breve B632 (DSM 24706) were safe and significantly reduced by more than a third the frequency of asthma exacerbations. At present, the first-line treatment of asthma is still drug-based, but specific strains of probiotics may be auxiliary remedies.